Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening - Santika, Rista; Indra Surya Diputra, Gde (Widya Manajemen, 2025)
Employee performance is one of the factors determining the success of a company in achieving its goals or objectives. To maintain and improve employee performance, motivation is necessary. Work motivation is a driving force or impetus within each individual to engage in activities so that they are willing to work using all their abilities and potential to achieve the desired goals. This study aims to determine the effect of work motivation on job satisfaction, to determine the partial effects of work motivation and job satisfaction on employee performance, and to examine the indirect effect of work motivation on employee performance through job satisfaction. The research was conducted at PT. BPR Artha Bali Jaya in Sukawati with a sample of 37 respondents. The research method used is quantitative. Data analysis techniques used in this study include Descriptive Analysis, Classical Assumption Test, Path Analysis, and Sobel Test. The results of the study indicate that work motivation has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, and work motivation has an indirect effect on employee performance through job satisfaction.